2017
DOI: 10.1002/mp.12415
|View full text |Cite
|
Sign up to set email alerts
|

Optical molecular imaging‐guided radiation therapy part 1: Integrated x‐ray and bioluminescence tomography

Abstract: Together with CT, BLT can provide precision radiation guidance and robust tumor volume assessment in small animal cancer research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It is imperative for us to develop the QBLT to accurately quantify the spatial distribution of the underlying tumor for radiation guidance. Recently, there are several studies showing the potentiality of applying BLT for radiation guidance (13,(19)(20)(21)(22). The significance of this work is that we devised a comprehensive approach to systematically tackle the known challenging of optical tomography for in vivo target delineation, quantify its uncertainties in both biology and tissue optics for localization, and present the practicality for radiation guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative for us to develop the QBLT to accurately quantify the spatial distribution of the underlying tumor for radiation guidance. Recently, there are several studies showing the potentiality of applying BLT for radiation guidance (13,(19)(20)(21)(22). The significance of this work is that we devised a comprehensive approach to systematically tackle the known challenging of optical tomography for in vivo target delineation, quantify its uncertainties in both biology and tissue optics for localization, and present the practicality for radiation guidance.…”
Section: Discussionmentioning
confidence: 99%
“…To bridge this gap and translate BLT-guided irradiation for practical use by investigators, we present a comprehensive study of achieving quantitative BLT (QBLT) that enables image-guided conformal irradiation based on 3D bioluminescence distribution in vivo. In this work, different from our and other groups' previous work (13,(19)(20)(21)(22), we made great effort not only optimizing hardware, algorithm, and calibration methods, but also quantifying biological variation and providing the approach of designing radiation margin for BLTguided RT.…”
Section: Introductionmentioning
confidence: 99%
“…Menichetti et al demonstrated the usefulness of [ 18 F]FET-PET guided boron neutron capture therapy in F98 rats [33]. However, several groups have been incorporating optical molecular imaging techniques such as bioluminescence and fluorescence imaging, to guide RT successfully [34–38]. Unfortunately, optical imaging has limited spatial resolution due to tissue absorption and scatter of visible light and background artifacts need to be taken into account caused by auto-fluorescence [39].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of reconstructed XFT images was assessed using CNR, DSC, and LE metrics (16,28). The CNR was…”
Section: Comparison Of Reconstruction Algorithmsmentioning
confidence: 99%